Management of Psoriasis in Children: a Narrative Review - Zohreh Hajheydari; Leila Sarparast; Soheila Shahmohammadi (Mazandaran University of Medical Sciences, 2015)
Psoriasis is an inherited chronic inflammatory papulosquamous disorder with a variable clinical spectrum affecting about 0.5% to 2% of children and adolescence. In spite of all performed researches around the world for seeking better treatments with fewer adverse effects to control the disease, there is still no cure for psoriasis. Treatment of psoriasis in children is very conservative and many therapies used for adults may not be appropriate for children due to possible long-term or delayed adverse effects. A wide range of therapeutic options are existed including; topical therapy, phototherapy, chemotherapy, systemic therapies and biologic therapies. Here in, because of the lack of data in this specific field of dermatology, we decided to review the current therapies of childhood psoriasis.